The effect of capital adequacy ratio and loan to deposit ratio on return on assets: Banking companies implementing green banking - Liyanita Dewi Kurnia; Ade Manggala Hardianto; Yuli Novitasari (Privietlab, 2026)
This study examines and analyzes the effect of the capital adequacy ratio and loan-to-deposit ratio on return on assets in the context of green banking, specifically for banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. This study aims to provide empirical evidence on how financial performance indicators, particularly the capital adequacy ratio and liquidity, influence bank profitability within the framework of sustainable banking practices. In this study, the capital aspect is measured using the capital adequacy ratio, which reflects a bank’s ability to absorb potential losses and maintain financial stability. The liquidity aspect is measured using the loan-to-deposit ratio, which indicates the bank’s effectiveness in channeling funds from deposits into loans. Meanwhile, profitability is measured using return on assets, which shows the bank’s ability to generate profits from its total assets. The data used in this research are secondary data obtained from published financial statements and annual reports of banking companies. The sampling technique applied is purposive sampling, based on specific criteria aligned with the research objectives, from a total population of 47 banking companies listed on the IDX, 12 companies were selected as the final sample, resulting in 36 observations over the three-year period. This study employs panel data regression analysis to examine the relationship between variables, and the data processing is conducted using E-Views version 13 software. Panel data analysis was chosen because it allows for a more comprehensive examination by combining cross-sectional and time-series data, thereby increasing the accuracy and reliability of the results. The findings of this study indicate that the capital adequacy ratio does not have a significant effect on return on assets in green banking. This suggests that the level of capital adequacy ratio held by banks does not necessarily determine their ability to generate profits from assets. Similarly, the loan to deposit ratio is also found to have no significant effect on return on assets, indicating that the bank’s level of liquidity and lending activities dose not directly influence profitability in the context of green banking. These conditions may play a more dominant role in determining bank profitability.